Numerical and experimental investigation of the runner channel vortex in Francis turbines regarding its dynamic flow characteristics and its influence on pressure oscillations. Issue 2 (March 2019) - Magnoli, M V; Anciger, D; Maiwald, M
Abstract: With the increasing demand for more flexibility in the operation of hydraulic machines, the operation range of Francis turbines has been progressively extended towards deep part load, where the channel vortex is present in the runner. Its set-in is often associated with increased pressure oscillation amplitudes in the vaneless space and runner. The runner channel vortex (RCV) is commonly observed during model test at reduced flow conditions. However, there is limited research available on its fluid dynamic fundamentals, on its origin, on its transition from incipient to fully developed vortical structure and on its relation to pressure oscillations. In order to acquire deeper understanding of the runner channel vortex phenomenon, computational fluid dynamic (CFD) simulations of the flow through the complete turbine were carried out. Several operating points along a given hill chart cross-section, starting from full load, passing through the optimum and part load and achieving deep part load, were calculated with the aim of observing the set-in and evolution of the runner channel vortex. The transient simulations made use of hybrid turbulence models, as scale adaptive simulation (SAS), to capture the fine dynamic flow characteristics with adequate accuracy. The numerical simulations can give some insight on the basics and fluid patterns related to the channel vortex, which cannot be directly observed at the model test rig. Nevertheless, the model test can deliver important information about the pressure oscillation amplitude in the hydraulic machine when the channel vortex is present. Moreover, special data of pressure oscillations at the model runner is available for selected projects. The test data offers the possibility to draw conclusions about the influence of the channel vortex on the pressure oscillation amplitude and delivers values for the validation and calibration of the CFD simulations. The numerical simulations and model test were done for a mid-specific speed Francis machine, for which pressure oscillation amplitudes were also measured at the model runner.